Pulmonary nocardiosis mimicking small cell lung cancer in ectopic ACTH syndrome associated with transformation of olfactory neuroblastoma: a case report - Keigo Kobayashi; Takanori Asakura; Makoto Ishii; Soichiro Ueda; Hidehiro Irie; Hiroyuki Ozawa; Kohei Saitoh; Isao Kurihara; Hiroshi Itoh; Tomoko Betsuyaku (BMC Pulmonary Medicine, 2018)
Abstract Background Pulmonary nocardiosis frequently develops as an opportunistic infection in cell-mediated immunosuppressive patients, and sometimes requires differentiation from pulmonary malignancy. Ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS) is a neoplastic disorder which leads to impaired cell-mediated immunity, and is commonly associated with small cell lung cancer (SCLC). Because pulmonary infection and causative malignancy can appear as pulmonary lesions with EAS, differentiation of these diseases remains a critical issue for physicians. Case presentation A 52-year-old woman with progressive lower limb paralysis and general fatigue was referred to us. She had been diagnosed with olfactory neuroblastoma (ONB) and treated with surgery and radiation therapy 10 years before the referral and had required stereotactic radiosurgery and chemotherapy 4 years later for a relapse of the ONB. On referral, she presented with Cushing’s syndrome with elevated cortisol and ACTH levels. Potassium supplement improved her symptoms; however, a month later, she was urgently hospitalized due to acute pleuritic chest pain on inspiration. Chest computed tomography revealed left lower lobular consolidations and a contralateral nodule in the right middle lobe. The clinical history and laboratory work-up suggested that her Cushing’s syndrome had most likely arisen from EAS. Additionally, the lungs were suspected as the ACTH source due to high levels of progastrin-releasing peptide and progressive pulmonary consolidation with a contralateral nodule, suggesting SCLC. However, histological examination from bronchoscopy revealed no evidence of malignancy, and Nocardia cyriacigeorgica was isolated from bronchoalveolar lavage fluid. Sulfamethoxazole/trimethoprim improved her pulmonary lesions. Somatostatin receptor scintigraphy revealed strong tracer uptake in the ONB lesions, indicating that the origin of the EAS was the olfactory tumor. However, histological examination of ONB specimens resected 10 years earlier showed no intracytoplasmic immunopositivity for ACTH. Conclusions We highlight a rare case of pulmonary nocardiosis, which was associated with EAS mimicking SCLC, and was related to ONB transformation. Nocardiosis has to be considered even though anamnestic, clinical, and radiological aspects suggest the presence of metastasis. Additionally, physicians should carefully monitor patients with ONB for the development of Cushing’s symptoms because the tumor can transform into an ACTH-producing form, even after long-term follow-up.